2002
DOI: 10.1073/pnas.222221899
|View full text |Cite
|
Sign up to set email alerts
|

Long-term systemic therapy of Fabry disease in a knockout mouse by adeno-associated virus-mediated muscle-directed gene transfer

Abstract: Fabry disease is a systemic disease caused by genetic deficiency of a lysosomal enzyme, ␣-galactosidase A (␣-gal A), and is thought to be an important target for enzyme replacement therapy. We studied the feasibility of gene-mediated enzyme replacement for Fabry disease. The adeno-associated virus (AAV) vector containing the ␣-gal A gene was injected into the right quadriceps muscles of Fabry knockout mice. A time course study showed that ␣-gal A activity in plasma was increased to Ϸ25% of normal mice and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…It is noteworthy that this level of organ a-gal A activity was higher (to our knowledge) than that of any other Fabry disease gene therapy experiments to date in all organs. 13,14,19,23,[31][32][33] This finding indicated efficient in vivo metabolic cooperativity of enzyme-deficient, affected cells from transduced and enzyme-overproducing cells (Table 1). These data also suggest that correction of only relatively a small number of key cells, such as repopulating HSPCs, may be sufficient to cure Fabry disease.…”
Section: Discussionmentioning
confidence: 84%
“…It is noteworthy that this level of organ a-gal A activity was higher (to our knowledge) than that of any other Fabry disease gene therapy experiments to date in all organs. 13,14,19,23,[31][32][33] This finding indicated efficient in vivo metabolic cooperativity of enzyme-deficient, affected cells from transduced and enzyme-overproducing cells (Table 1). These data also suggest that correction of only relatively a small number of key cells, such as repopulating HSPCs, may be sufficient to cure Fabry disease.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we demonstrate that selective MC4R knockdown in PVN neurons of the adult wild-type rat results in no changes in food intake and body weight when animals are fed with a regular diet within 2 weeks, but causes increased feeding and excessive weight gain in response to a high-fat diet. It is unlikely that the unaltered feeding and body weight in response to the regular diet is due to insufficient gene suppression because AAV-mediated gene expression occurs within 3 days (Flotte et al 1993, Takahashi et al 2002 and AAV-mediated effective gene silencing has been reported at days 6-10 after injection of AAV-shRNA (Hommel et al 2003, Wang et al 2006, Paskowitz et al 2007). Thus, our results suggest that the disruption of MC4R in PVN neurons increases the sensitivity to diet-induced hyperphagia and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…19 HSPGs are critical regulators of growth and differentiation of epithelial and connective tissues for which AAV has a specific tropism. [20][21][22][23][24] Moreover, HSPGs function as coreceptors promoting cytokine signaling in normal B cells in the context of antigen-specific B-cell differentiation. Besides activation of the BCR, CD40 was shown to control the expression of HSPGs on tonsillar B cells.…”
Section: Discussionmentioning
confidence: 99%